Boosting capacitive charge storage of 3D-printed micro-pseudocapacitors via rational holey graphene engineering. (December 2019) - Tian, Xiaocong; Tang, Kang; Jin, Hongyun; Wang, Teng; Liu, Xiaowei; Yang, Wei; Zou, Zhicheng; Hou, Shuen; Zhou, Kun
Abstract: Micro-pseudocapacitors (MPCs) are prospective power source candidates with compatible sizes as well as superior power densities for miniaturized electronic devices; however, their limited capacitive charge storage characteristics are still hindering their further development. Herein, an optimized 3D printing technique is employed to build remarkable reduced holey graphene oxide (rHGO) supported MPC microelectrodes. In such microelectrodes, the presence of macroscale pores introduced through freeze drying is beneficial to the accessibility to electrolyte ions. Moreover, with two additional pore modals including the microscale pores from pseudocapacitive nanoparticles stacking and nanoscale in-plane holes formed by rational HGO engineering, the MPC microelectrodes offer an enhancement in both electrical and ionic transports. The resultant 3D-printed planar MPCs exhibit a remarkable device specific charge storage capacity of 241.3 mC cm −2, which is approximately 1.7-fold that of a non-optimized one and much higher than most reported planar micro-supercapacitors. Superior rate capability and high capacity retention (91% capacity retention after 11000 charge and discharge cycles) are also achieved. Our porosity engineering strategy combined with 3D printing is expected to serve as a facile and general design in the roadmap for next-generation state-of-the-art customized electrochemical energy storage devices. Graphical abstract: Image 1